Opportunities and challenges in conducting secondary analysis of HIV programmes using data from routine health information systems and personal health information. (20th July 2016) - Gloyd, Stephen; Wagenaar, Bradley H; Woelk, Godfrey B; Kalibala, Samuel
Abstract : Introduction: HIV programme data from routine health information systems (RHIS) and personal health information (PHI) provide ample opportunities for secondary data analysis. However, these data pose unique opportunities and challenges for use in health system monitoring, along with process and impact evaluations. Methods: Analyses focused on retrospective case reviews of four of the HIV‐related studies published in this JIAS supplement. We identify specific opportunities and challenges with respect to the secondary analysis of RHIS and PHI data. Results: Challenges working with both HIV‐related RHIS and PHI included missing, inconsistent and implausible data; rapidly changing indicators; systematic differences in the utilization of services; and patient linkages over time and different data sources. Specific challenges among RHIS data included numerous registries and indicators, inconsistent data entry, gaps in data transmission, duplicate registry of information, numerator‐denominator incompatibility and infrequent use of data for decision‐making. Challenges specific to PHI included the time burden for busy providers, the culture of lax charting, overflowing archives for paper charts and infrequent chart review. Conclusions: Many of the challenges that undermine effective use of RHIS and PHI data for analyses are related to the processes and context of collecting the data, excessive data requirements, lack of knowledge of the purpose of data and the limited use of data among those generating the data. Recommendations include simplifying data sources, analysis and reporting; conducting systematic data quality audits; enhancing the use of data for decision‐making; promoting routine chart review linked with simple patient tracking systems; and encouraging open access to RHIS and PHI data for increased use.